Toward a metadata model for research information management systems. Issue 3 (12 June 0018) - Lee, Dong Joon; Stvilia, Besiki; Wu, Shuheng
Abstract : Purpose: The purpose of this paper is to examine the relationships between researcher characteristics and their use of metadata in their ResearchGate profiles. Design/methodology/approach: This paper reports on one part of a larger study that examined researchers' use of and engagement with research information management systems (RIMSs). The study's design included qualitative, semi-structured interviews with 15 researchers and a survey completed by 412 researchers. Detailed reports of findings from the interviews and survey can be found elsewhere. This paper reports on the part of the study that analyzed the use of metadata elements in the ResearchGate profiles of 126 survey participants. Findings: Most researchers shared metadata related to their research rather than their teaching or service. Statistical analyses revealed statistically significant relationships between researchers' metadata use and their participation levels in RIMSs, as well as between metadata use and researchers' seniority. Originality/value: The study's findings help to identify researchers' priorities for different metadata elements, as well as to construct profile metadata templates for each specific participation level.